Clausoxamine, an alkaloid possessing a 1, 3-oxazine-4-one ring from the seeds of Clausena lansium and the anti-obesity effect of lansiumamide B. Issue 74 (4th October 2017) - Huang, Li; Li, Dan; Xu, Yun-Shao; Feng, Zhe-Ling; Meng, Fan-Chen; Zhang, Qing-Wen; Gan, Li-She; Lin, Li-Gen
Abstract : One alkaloid with an unprecedented skeleton and one alkaloid with anti-obesity effect were isolated from the seeds of Clausena lansium . Abstract : A novel alkaloid, clausoxamine (1 ), which possesses an unprecedented 1, 3-oxazinan-4-one ring, was isolated from the seeds of Clausena lansium, along with six known analogues. The structure and absolute configuration of1 were established on the basis of detailed NMR and HRESIMS analysis, as well as comparison of its experimental and TD-DFT calculated ECD spectra. A proposed biosynthetic pathway was predicted for compound1 . The major alkaloid, lansiumamide B, was found to reduce fat mass gain and improve insulin sensitivity on high fat diet treated mice, which might be a potential anti-obesity and insulin sensitizing agent.